PEMANFAATAN KAYU MANGROVE OLEH MASYARAKAT SUKU ASLI SUNGAI LIONG PULAU BENGKALIS - Miswadi, Miswadi; Firdaus, Ramses; Jhonnerie, Romie (Dinamika Maritim, 2017)
Mangrove wood is the main source indigenous communities (Suku Asli) to meet the economic needs of their household. Our purposes were to describe the level of used of mangrove wood by indigenous communities at Liong River, Bengkalis Island during February to May 2014. Primary data were collected through observation and interview then data described descriptively. Results showed that mangrove woods utilized by the communities to meet the raw material of mangrove charcoal and stakes needs as the main uses while fire woods additional benefit for them. The woods rate collection was found different and influenced by tidal conditions. During spring tide they might collected 700-750 kg/person/ and 70-80 logs/person/day for charcoal and stakes respectively, while neap tides they collected 600-650 kg/person/day and 40-50 logs/person/day. We concluded that exploitation of mangrove wood in the Liong River was very high. There should be restrictions on the numbers of mangrove wood utilization, for sustainable uses.